Differential innate immune activation by four different CpG-ODNs in porcine and murine cells: Implications for vaccine design - Vedelago, Giuliana (2025)
Synthetic oligodeoxynucleotides containing unmethylated cytosine-guanine motifs (CpG-ODNs) are immunostimulants widely used as vaccine adjuvants. This study evaluated the innate immune responses induced by four CpG-ODNs: [2395 (class C), 1826, 1018, and 2007 (class B)] in porcine and murine cells, representing species of veterinary and preclinical interest, respectively. Porcine peripheral blood mononuclear cells and murine splenocytes were stimulated in vitro with each CpG-ODN, and the mRNA expression of IL-6, IL-12p40, IFN-β, IFN-γ, TNF, and TLR9 was assessed by RT-qPCR. In porcine cells, only CpG-ODN 2395 significantly upregulated IL-6, IL-12p40, and TLR9. In murine cells, all CpG-ODNs induced IL-6; CpG-ODNs 2395, 1826, and 1018 upregulated IL-12p40; and only CpG-ODN 2395 induced TLR9. Stimulation with CpG-ODNs 2395 and 1018 enhanced IFN-β and IFN-γ expression in porcine cells. In contrast, murine cells showed increased IFN-β levels in response to CpG-ODNs 2395 and 1826, and upregulated IFN-γ following stimulation with CpG-ODNs 2395, 1826, and 1018. TNF expression was exclusively induced in porcine cells by CpG-ODN 1018, 2395, and 2007. Notably, CpG-ODN 1826 exhibited species-specific activity in mice, inducing IL-6, IL-12p40, IFN-β, and IFN-γ. These findings reveal significant interspecies differences in CpG-ODN-induced immune responses, emphasizing the importance of species-specific considerations when selecting CpG-ODNs as vaccine adjuvants for preclinical and veterinary applications.